Access to antibiotics without prescription in community pharmacies in Yemen during the political conflict - Halboup, Abdulsalam; Abdi, Abdikarim; Ahmed, Mayada; Al-Qadasi, Fadhl; Othman, Gamil Q. (Elsevier, 2020)
Objectives The practice of dispensing non-prescribed antibiotics aggravates the global burden of antibiotic resistance. The objective of this study is to assess the practice of community pharmacists regarding dispensing antibiotics without a prescription based on simulated clinical scenarios. Study design Cross-sectional study. Methods The study was performed between 15 April to 18 June 2015. Five different clinical scenarios were simulated, involving sore throat, otitis media, cough, diarrhea, and urinary tract infection (UTI). Three different levels of demand were used to convince the pharmacists to dispense antibiotics data was analyzed using SPSS, version 21.0. Results Two-hundred community pharmacies in Sana'a were visited for each clinical scenario. The majority of pharmacies (73.3%) dispensed antibiotics without medical prescriptions in different levels of demand. Most antibiotics were dispensed for the sore throat simulated scenario (99.5%), followed by cough (92%), diarrhea (75.5%), and otitis media (52%). The lowest percentage of dispensed antibiotics was in the UTI scenario, with 48%. Among the pharmacists who dispensed antibiotics, 74.2% provided an explanation to the simulated patients regarding how to use antibiotics, 77.6% counseled the patient about treatment duration and only 11.9% of the pharmacists asked about the pregnancy status. Regarding the cough scenario, 83% of the pharmacists inquired about the type of cough before dispensing medication. Conclusion Antibiotics in Yemen can be easily obtained without medical prescription or evidence-based indication.